Pendampingan dan Penguatan Proyek Profil Pelajar Pancasila dalam Kurikulum Merdeka di Madrasah Aliyah AIAI - Padlun Fauzi; Tsulis Amiruddin Zahri; Muhammad Hijran; Dini Oktariani; Mustofa Tohari; Khadijah Khadijah (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Mentoring and strengthening the Pancasila Student Profile Project (P5) in the Independent Curriculum is a strategic step to form a generation with character in accordance with Pancasila values. Mentoring is carried out through training, monitoring, and evaluation involving educators, students, and madrasa stakeholders. The results show a significant increase in teachers' understanding and ability in designing and implementing P5. In addition, students showed positive developments in aspects of independence, social responsibility, and critical thinking skills in accordance with the Pancasila student profile. This study recommends continued support to make P5 an integral part of the madrasah learning culture in order to realize national education goals. This collaborative approach is expected to strengthen the achievement of national education goals in the Independent Curriculum, especially in the area of religious-based education.